Variations in muscle activation timing with changes in pedal technique - Loveday, D. E.; Drayer, K. A.; Pierotti, D. J.; Coast, J. R. (International Journal of Performance Analysis in Sport, 2008)
The current study was designed to determine the effect of altering pedaling technique on muscle activation timing and duration. Eight subjects performed three trials (same day) utilizing a natural, dorsiflexed and plantarflexed pedaling technique while the timing of the gastrocnemius lateralis (GL), tibialis anterior (TA), biceps femoris (BF) and vastus lateralis (VL) muscle activation / deactivation were measured with electromyography (EMG). These data were compared to crank arm orientation. BF muscle deactivation under the plantarflexed pedaling condition was significantly delayed (P <0.05) by an average of 23º when compared to the dorsiflexed condition. Although there were changes under the altered pedaling conditions for the other muscles measured, which included increased VL and BF range during plantarflexion, delayed activation and decreased range for the GL during plantarflexion and early TA activation under both dorsiflexion and plantarflexion, none were significant.